Psychology in Latin America: Current status, challenges and perspectives - Pérez-Acosta, Andrés M.; Consoli, Andrés J. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
Book Review: Ardila, R. (Ed.) (2018). Psychology in Latin America: Current status, challenges and perspectives. Cham, Suiza: Springer Nature.